Comparison of electrocardiogram parameters and echocardiographic response between distinct left bundle branch area pacing modes in heart failure patients - Li, Yao; Zhang, Wei; Chen, Keping; Lian, Zhexun (Frontiers in Cardiovascular Medicine, 2024)
Background Left bundle branch area pacing (LBBAP) has become an alternative method for cardiac resynchronization therapy. Various modes of LBBAP have been determined, including left bundle trunk pacing (LBTP), left anterior branch pacing (LAFP) and left posterior branch pacing (LPFP). However, whether the outcomes of various pacing modes differ in heart failure (HF) patients is still unclear. This study aimed to compare the electrophysiological characteristics and echocardiographic response rate among those distinct modes of LBBAP. Methods HF patients undergoing successful LBBAP were retrospectively included. Distinct modes of pacing were determined based on paced QRS morphology. The fluoroscopic images were collected to compare the lead tip position between the groups. The electrocardiograms (ECG) before and after LBBAP were used to measure the depolarization (QRS duration [QRSd] and the interventricular delay [IVD]), and the repolarization parameters [QTc, TpeakTend(TpTe), and TpTe/QTc]. The left ventricular ejection fraction (LVEF) and left ventricular end-diastolic diameter (LVEDD) of patients were also recorded. In addition, the lead parameters and certain complications were compared. Results A total of 64 HF patients were finally included, consisting of 16 (25.0%) patients in the LBTP group, 22 (34.4%) patients in the LAFP group, and 26 (40.6%) patients in the LPFP group. The distribution features of LBBAP lead tips were significantly related to pacing modes: LBTP was more likely to be in zone 4 while LAFP or LPFP was prone to locate in zone 5. After LBBAP, the ventricular ECG parameters were significantly improved, regardless of pacing modes. Besides, the LVEF of the patients was significantly increased (P < 0.001), and LVEDD was significantly decreased (P < 0.001). There was no difference in the response rate and super-response rate among groups (P > 0.05). In addition, the lead parameters remained stable and no significant difference was observed among groups. Conclusion LPFP was the main pacing mode among HF patients after LBBAP. The paced QRS morphology was significantly related to the position of lead tips. After LBBAP, the ventricular depolarization synchronization and repolarization stability were both significantly improved, regardless of pacing modes. There was no significant difference in the echocardiographic response rate among distinct LBBAP modes.